Boxers' training process design and content within half-year training macrocycle - Rudenko, G. V.; Mokeev, G. I. (Theory and Practice of Physical Culture, 2017)
Subject to the study was a half-year pre-season training macro-cycle of the elite boxer who won the Russian Boxing Championship. Each of the two tree-month training periods was broken down into three monthly training stages, with the staged training process design and contents being analysed and followed by the data arrays being summarized for the whole six-month cycle. The periodic design of an athletic training process may be viewed as natural for a sport fitness building process and, as verified by the authors` practical experience, facilitating for the boxers` precompetitive training process. The proposed training process design model was tested in the precompetitive training process of the Saint Petersburg Mining University boxing team. The training process model was proved successful as verified by the high competitive accomplishments of the subject boxers in the 2016 top-ranking events.